A strategy that combines a hydrogel and graphene oxide to improve the water-lubricated performance of ultrahigh molecular weight polyethylene. (February 2021) - Wang, Chaobao; Bai, Xiuqin; Guo, Zhiwei; Dong, Conglin; Yuan, Chengqing
Abstract: The use of water-lubricated materials is important in efforts to protect the environment and conserve resources. However, the low bearing capacity and insufficient lubrication of ultrahigh molecular weight polyethylene (UHMWPE), which is an important water-lubricated material, restrict its application in engineering fields. In order to improve the properties of UHMWPE under water lubrication, we propose a strategy that combines a soft polyacrylamide (PAAm) hydrogel with hard graphene oxide (GO). PAAm-GO flakes were synthesized and UHMWPE composites reinforced with GO or PAAm-GO were prepared. The mechanical properties and tribological performances of the composites were tested and analyzed. The results show that the PAAm layers grafted onto GO played an important role in improving the bearing capacity and lubrication conditions of the composites. The strategy of integrating hard GO flakes modified with soft PAAm layers will provide a method for designing reinforced composites used in the manufacturing of water-lubricated bearings.